Insights on COVID-19 impacts, challenges and opportunities for India's biodiversity research: From complexity to building adaptations. (March 2021) - Ramvilas, Ghosh; Dhyani, Shalini; Kumar, Biju; Sinha, Neha; Raghavan, Rajeev; Selvaraj, Gayathri; Divakar, Nithin; Anoop, V.K.; Shalu, Kannan; Sinha, Alolika; Kulkarni, Apoorva; Das, Sandeep; et al.
Abstract: The COVID-19 pandemic has impacted every sphere of human society. The paradigm shift of focus to COVID-related research and management has significantly affected various scientific domains, including biodiversity conservation. We assessed the perceptions of early-career researchers working for biodiversity conservation across India, to understand the impacts of the ongoing pandemic on their research. We administered an online questionnaire survey to 565 respondents, who identified four key areas that are affected by the pandemic: (1) research, (2) conservation (3) education, and (4) communication and networking. Respondents (89.2%) perceived that their fieldwork, followed by travel for meetings and funding were the most affected due to COVID-19 outbreak and subsequent lockdown. Nonetheless, responses on the impact varied between different professional categories and were disproportionate. Our study highlights that majority of the respondents (80%) advocate for stakeholder-driven policies and management practices as the most effective strategy to promote biodiversity conservation, in the post-COVID-19 world. To this end, as a post-pandemic response, we propose holistic solutions such as optimising research funding and collaborations, and supporting and strengthening them by citizen science and big data analytics. Our findings and recommendations will also serve as a paradigm for post-COVID-19 biodiversity policy, advocacy and implementation of the post 2020 biodiversity action plan that supports eco civilization.